A Gel Polymer Electrolyte for Aluminum Batteries. Issue 8 (30th June 2021) - Elia, Giuseppe Antonio; Acevedo, Carlos Islas; Kazemi, Reyhaneh; Fantini, Sebastien; Lin, Rongying; Hahn, Robert
Abstract : Herein, the use of a gel polymer electrolyte (GPE) comprising polyacrylonitrile and 1‐ethyl‐3‐methylimidazolium chloride:aluminum trichloride (EMIMCl:AlCl3 ) ionic liquid in aluminum batteries is investigated. The investigated GPE is characterized in terms of conduction properties. The obtained ionic conductivity values are suitable for battery applications. The ability of the GPE to sustain an efficient aluminum stripping deposition process is verified, revealing the need of a swelling process to enable the aluminum plating/stripping. The mitigation of the chloroaluminate corrosivity in the GPE is confirmed by evaluating the corrosion current of stainless steel 316 current collectors. The long‐term ability of GPE to sustain the stripping deposition process is tested, evidencing a good Al/GPE interface stability. Finally, the GPE electrolyte suitability in the Al battery is verified by assembling an Al/GPE/pyrolytic graphite (PG) cell. The test cell shows a good cycling ability, demonstrating the suitability of the GPE electrolyte for the realization of aluminum batteries. Abstract : A gel polymer electrolyte (GPE), comprising polyacrylonitrile and 1‐ethyl‐3‐methylimidazolium chloride:aluminum trichloride (EMIMCl:AlCl3 ) ionic liquid, capable of sustaining the aluminum stripping deposition process is developed. The proposed GPE mitigates the chloroaluminate corrosivity against stainless steel 316 current collectors. Al/GPE/pyrolytic graphite (PG) cell operation is successfully demonstrated.